Bibliometric Analysis: Digital Literacy in Sharia Business - Karisma, Ayu (International Journal of Economics Studies, 2025)
The publication of scientific publications will continue to increase the number of publications every year, which shows that the development of science and knowledge is increasing. If a research topic experiences an increase in publications every year, it shows that the topic is interesting to research. Researchers need to know a topic that is always experiencing an increasing trend in order to conduct further research related to that topic, one way is by conducting bubliometric analysis. The purpose of this study is to examine the development of research trends related to the topic of digital literacy in Sharia business. The method used in this study is bibliometric analysis, data collection in the study is carried out by searching through Scopus with the keyword: "digital literacy and sharia business" then mapping is carried out through vosviewer. The entire data is exported in CSV format with a total of 378 documents. The findings of this study show that the number of research on the topic of digital literacy in the development of MSMEs has increased over the last five years in 2020-2024. The results of the analysis show that research topics related to digital literacy in Sharia business have experienced publication development over the past five years, and the highest publication in 2024. The most prolific writer is Basrowi with 8 documents. Indonesia is the country that produces the most research on the topic of digital literacy in Sharia business. The research trend related to the topic of digital literacy in sharia business is experiencing publication development every year, showing that this topic is interesting to be researched in the future.